Vanadium-doped and mixed Si/Ge-based apatites : synthesis, crystal chemistry and ionic conductivity - Li, Henan (2014)
Apatite-type oxides taking the general formula [AI4][AII6][(BO4)6][X2±y], particularly those of the rare earth silicate and germanate systems, are among the more promising materials being considered as alternative solid oxide fuel cell electrolytes. Nonstoichiometric lanthanum silicate and germanate apatites display pure ionic conductivities exceeding those of yttria-stabilized zirconia at moderate temperatures (500 – 800 ºC). Indeed, it is the underlying complexity and flexibility of these substances that endows them with such promise as ion conductors. Many factors influence the ionic mobility, the most important being the concentration of cation vacancies and excess anions incorporated in the structure, the valence and atomic size of the substitutional elements, crystal/grain orientations, and phase purity. In this thesis, the main focus falls on the synthesis and characterization of various apatite electrolyte materials and establishing underlying correlations between oxygen ion percolation and crystal chemistry. Apatites can be synthesized in various ways, including solid state sintering, sol-gel methods and hydrothermal reactions. The former is favored since large quantities are readily fabricated for division and multi-technique characterization, while the latter has the advantage of lower synthesis temperature. This thesis examined two synthesis methods (solid state and hydrothermal) for powdered apatites, and the growth of single-crystal apatites for investigating anisotropic ion migration. Laboratory X-ray, synchrotron, and neutron diffraction were employed to refine crystal structures by the Rietveld method. The microstructures, local structures and chemical compositions were analyzed by electron diffraction, spectroscopic and microscopic methods.